The Phenomenon of Political Dynasties in Regional Head Elections and Their Impact on Democracy in Indonesia - Pratiwi , Ni Putu Ika Armitha; Widyantara, I Made Minggu (Indonesian Journal of Law and Justice, 2025)
The aim of this research is to study how dynastic politics affects democratic principles, including fair competition, community participation, and accountability of regional heads to the people. This research uses a qualitative descriptive approach, utilizing secondary qualitative data which is explained descriptively to answer research questions. The results of this research state that dynastic political practices in Indonesia damage the integrity of democracy and regional government by concentrating power in one family, ignoring the qualifications of other candidates, and hindering healthy political competition.